Reação de variedades de cana-de-açúcar (Saccharum spp.) aos nematóides de galhas e de lesões radiculares - Santos, Daniela Alves dos (2010)
The cultivation of sugar cane grows at a rapid pace in various regions of Brazil. However, it is important to note that many pathogens may be limiting the production of this culture, among them the root-knot nematodes (Meloidogyne spp.) and the root lesions nematodes (Pratylenchus spp.), which are spread across almost all the agricultural regions in the country. Among the control methods to reduce the population of these organisms in sugar cane, it is mentioned the use of resistant varieties, but there is a lack of information about their reaction over the nematodes mentioned above. Thus, the objective of this study was to evaluate the susceptibility of varieties of sugarcane to Meloidogyne incognita, M. javanica, M. paranaensis, Pratylenchus zeae and P. brachyurus. For this purpose, seedlings of these varieties were inoculated with 4000 eggs, for the genus Meloidogyne, or 500 specimens, for Pratylenchus, the inoculed plants were maintained at a greenhouse for 60 days. Subsequently, the plants were removed from the pots and measured for height, fresh and dry weight from the shoot, fresh root and final population of nematodes in the root system, to calculate the reproduction factor (FR). After the removal of sugarcane plants, each pot received a seedling of tomato cv. Santa Cruz Kadá or corn cv. Milho Verde, for the biotest of Meloidogyne and Pratylenchus, respectively. The results indicated that the varieties showed no immune reaction. The variety CTC 17 showed FR <1, for to M. incognita, however, it was among those that had the greatest reductions in the vegetation parameters. The greatest FR for M. incognita, M. javanica and M. paranaensis were to the varieties CTC 5 (FR = 3,9), RB946016 (FR = 4,6) and CTC 15 and RB72454 (FR = 3,3), respectively. For P. brachyurus the lowest RF was observed for CTC 4, which was the only cultivar with RF <1 for this nematode, while the most susceptible varieties were CTC5, CTC 15 and CTC 16, which presented FR> 3. As for the RB group, higher FR were for RB976933, RB835054 and RB956911, which were equal to 2.9. For P. zeae, the FR ≥ 3.0 was observed for CTC 13, CTC 14, CTC 15, CTC 16 and RB855156. The greatest susceptibility to the nematodes was not always associated with greater reductions in the parameters height, fresh and dry weight of the shoot and fresh weight of the root, indicating, in some cases, different levels of tolerance.